The INI African regional nitrogen centre: challenges and opportunities in Africa - Masso, C.; Bekunda, Mateete A.; Mngube, F.M. (Springer, 2020)
The International Nitrogen Initiative (INI) aims at optimizing nitrogen (N) use in food and energy production, while minimizing environmental risks. In Africa, nitrogen management must address the ‘too little’ and ‘too much’ paradox. Too little nitrogen is used in food production, which has led to chronic food insecurity and malnutrition. Conversely, too much nitrogen load in water bodies due mainly to excessive soil erosion, leaching, limited nitrogen recovery from wastewater, and from atmospheric deposition, still contributes to eutrophication in some areas. Significant research has been conducted to improve N use for production, whereas little has been done to be effective in addressing the ‘too much’ issue. The current research gaps must be addressed, and supportive policies operationalized, to maximize nitrogen benefits, while reducing the negative impacts of nitrogen on the environment. Innovation platforms involving key stakeholders in Africa are required to address the full chain of nitrogen use efficiency.